Leaving one dream to achieve another: one lecturer's PhD journey - Wan Mohd Nor, Murni (MPWS Rich Publication, 2017)
Dr Murni Wan Mohd Nor has had a long interest in issues of public interest and human rights. She holds a Masters in Comparavite Law before resuming her PhD on issues of hate speech, the harms it brings and the need for specific legislation. Dr Murni cares deeply for fostering racial unity and interfaith understanding; having written a number of published articles on the matter and organised successful interfaith dialogue sessions. Despite these achievements, she believes her greatest accomplishment takes form in her family, particularly her 2 young children. This book explains Murni's initial aspirations of being a human rights lawyer, and why she decided to leave behind a promising career in the legal world for an academic one. The author gives a very real description of what lies beneath the "glamorous" PhD title - the lonely years of postgraduate life, the sense of helplessness in finishing her thesis while managing personal and financial problems, and other struggles faced during her academic journey. But she persevered and achieved her dream of obtaining her PhD before the age of 30, with her husband and daughter by her side. It is hoped that this book will provide motivation to others - not only those doing / about to do their PhD, but to those who are about to take a leap of faith... to those undergoing a terrifying but exhilirating change... to those who love their partners but are finding themselves in a very rough patch... to those who chose to follow their dreams but suddenly doubt if the choice they had made was the right one... then this book may be perfect for you.